An exploration of the use of tactical officers in three Canadian police services. (December 2021) - Jenkins, Bryce; Semple, Tori; Bennell, Craig; Huey, Laura
In order to better understand the use of tactical police resources in Canada we interviewed patrol and tactical officers ( N = 28) from three Canadian police services. A thematic analysis indicated that tactical officers are primarily responding to calls beyond the capabilities of patrol to resolve optimally which included high-risk calls as denoted by the presence of risk-factors and calls unfolding in special environments . Further, tactical officer response is thought to result in a reduced threat to officer and public safety . Our findings suggest that in contrast to previous claims, tactical officers are often responding to calls where significant risk is present.